1992
DOI: 10.1099/00221287-138-12-2609
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the spoIIIJ gene of Bacillus subtilis: a vegetatively expressed gene that is essential for  G activity at an intermediate stage of sporulation

Abstract: The spo-87 mutation is one of two sporulation mutations originally used to define the spUJ locus of Bacillus subtiIis. We now show that it blocks sporulation after completion of prespore engulfment (stage 111). Surprisingly, the operon is expressed vegetatively, probably from a @*-dependent promoter, and its expression is shut down at the transcriptional level at about the onset of sporulation. DNA sequencing reveals that the locus defined by sp0-87, which we now designate spIIIJ, consists of a bicistronic ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
112
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 40 publications
2
112
0
1
Order By: Relevance
“…Moreover, each homolog can have multiple functions and reaction mechanisms (7,(36)(37)(38). We envision that the peculiarity of having a hydrophilic cavity in the membrane may be a common feature conserved in many of the family members.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, each homolog can have multiple functions and reaction mechanisms (7,(36)(37)(38). We envision that the peculiarity of having a hydrophilic cavity in the membrane may be a common feature conserved in many of the family members.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that G accumulates but is mostly inactive in spoIIIA or spoIIIJ mutants of B. subtilis (19,41), both of which show a morphological block just after completion of the engulfment process (6,30). This has led to the suggestion that both spoIIIA and spoIIIJ act after engulfment to promote the activation of G in the prespore.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusion of the engulfment process is not sufficient for the activation of G , which further requires expression of several genes, including the eight cistrons of the spoIIIA operon and the spoIIIJ gene (6,19,34). G accumulates in spoIIIA or spoIIIJ mutant cells but is unable to activate transcription from its target promoters (19,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus two homologues (Spy0247 and Spy0351) were identified of B. subtilis SpoIIIJ (Errington et al, 1992), a probable Lpp that has recently been suggested to be associated with the export and processing of integral membrane proteins (Tjalsma et al, 2000 ;Luirink et al, 2001 ;Yen et al, 2001). Both Spy0247 and Spy0351 are predicted to encode proteins with multiple MSDs in addition to the predicted Nterminal lipid anchor, as in SpoIIIJ (Luirink et al, 2001 ;Yen et al, 2001).…”
Section: Summary Featuresmentioning
confidence: 99%